MARKETING IN THE XXI CENTURY: FROM FINDING A CUSTOMER FOR BUSINESS TO FINDING «NECESSARY» BUSINESS FOR THE CUSTOMER - Kotelnikov, Alexandr; Nozdreva, Irina; Koshevenko, Svetlana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The research aim of the paper is to review and to describe best practices for marketing and to highlight the characteristics of marketing-management. System analysis, analytical and comparative methods were used for this research. The paper deals with marketing changes, which have been happening in the business community for last years. Nowadays a number of companies define marketing as a basis for management decision-making, abandoning the traditional model in which marketers were only focused on selling already produced goods. The authors of the paper consider that such a model is the future of a client-oriented business. Using this model, the company's marketing structures are connected at the stage of creating a new product and are actively involved in its entire life cycle. This concept allows companies to create a necessary product for the consumer, and sometimes to anticipate his/her needs, which makes the companies stand out from the majority of competitors. The paper also notes that in our society the main values of companies are not production facilities that are owned, but intellectual resources and the ability to use information about customers. Thus, the development of the brand and focus on the consumer, rather than building up physical assets, becomes the main driving force of the company's development. The companies that learn how to handle a huge amount of information about their customers and anticipate their needs, creating new products and services, will be able to succeed in a highly competitive environment.